Developing a Commercial Ethics Framework for Analysing Marketing Campaigns - Santos, Vasco (2021)
This study integrates the relationship of business ethics in marketing campaigns and the importance of the repercussion on organizational performance with the aim of creating a guide of business ethics in marketing campaigns for small and medium enterprises (SMEs). This guide allows SMEs to analyse their ethical dimension as well as to raise awareness and instill commercial ethics actions in the marketing campaign common practices in organisations. The qualitative methodology has been applied, and the proposed theoretical model uses a set of dimensions of ethics, commercial ethics, codes of conduct, marketing, and marketing campaigns to analyse the relationship of commercial ethics with marketing campaigns and its influence on organisations. The result demonstrates the influence of commercial ethics on advertising actions that, when applied positively, enable and promote the brand image, thus contributing to the organizational performance.